DisProt 7.0: a major update of the database of disordered proteins. Issue Volume 45:Issue D1(2017) (24th November 2016) - Piovesan, Damiano; Tabaro, Francesco; Mičetić, Ivan; Necci, Marco; Quaglia, Federica; Oldfield, Christopher J.; Aspromonte, Maria Cristina; Davey, Norman E.; Davidović, Radoslav; Dosztányi, Zsuzsanna; Elofsson, Arne; Gasparini, Alessandra; et al.
Abstract: The Database of Protein Disorder (DisProt, URL: www.disprot.org ) has been significantly updated and upgraded since its last major renewal in 2007. The current release holds information on more than 800 entries of IDPs/IDRs, i.e. intrinsically disordered proteins or regions that exist and function without a well-defined three-dimensional structure. We have re-curated previous entries to purge DisProt from conflicting cases, and also upgraded the functional classification scheme to reflect continuous advance in the field in the past 10 years or so. We define IDPs as proteins that are disordered along their entire sequence, i.e. entirely lack structural elements, and IDRs as regions that are at least five consecutive residues without well-defined structure. We base our assessment of disorder strictly on experimental evidence, such as X-ray crystallography and nuclear magnetic resonance (primary techniques) and a broad range of other experimental approaches (secondary techniques). Confident and ambiguous annotations are highlighted separately. DisProt 7.0 presents classified knowledge regarding the experimental characterization and functional annotations of IDPs/IDRs, and is intended to provide an invaluable resource for the research community for a better understanding structural disorder and for developing better computational tools for studying disordered proteins.